History of the Renovation of Abdulazizkhan Madrasah - Abdullayeva, Dilfuza (Researchparks Publishing, 2023)
This article covers the history of protection, repair and restoration of Abdulazizkhan madrasa during the 20-80s of the 20th century.Also, on the basis of the documents of the National Archives of Uzbekistan and the State Archives of Bukhara Region, the issues such as the scope of the renovation of the madrasa, the allocated funds, and the exploitation of the monument have been clarified.